Comparison of laparoscopic pyeloplasty vs. robot-assisted pyeloplasty for the management of ureteropelvic junction obstruction in children - Pérez-Marchán, Marcos; Pérez-Brayfield, Marcos (Frontiers in Pediatrics, 2022)
Background: Ureteropelvic junction obstruction (UPJO) is a commonly observed abnormality in pediatric urology. Minimally invasive approaches have gain popularity in recent years. Studies have demonstrated excellent results with both laparoscopic pyeloplasty (LAP) and robot-assisted pyeloplasty (RAP). Few studies have compared the experience of both procedures performed in a single institution. Our objective is to compare laparoscopic pyeloplasty and robot-assisted pyeloplasty in the Puerto Rican pediatric population. Methods: We conducted a retrospective cohort study using our clinic’s database on patients with UPJO that were operated by the same surgeon (MPB) from 2008 to 2019. With this data, statistical analysis was conducted of demographics, preoperative studies, perioperative data and complications of both procedures. This study was approved by our local IRB committee. Results: A total of 86 patients that underwent pyeloplasty with at least 3 years of follow up were recorded for this study. Laparoscopic pyeloplasty and robot-assisted pyeloplasty were performed in 44 (51.1%) and 42 (48.8%) patients, respectively. Significant differences between preoperative and postoperative hydronephrosis grading were observed in both LAP and RAP groups. However, no significant difference was seen regarding reduction of hydronephrosis grading when comparing both groups. Discussion: Our study revealed that robotic assisted pyeloplasty (RAP) and laparoscopic pyeloplasty (LAP) are comparable in operative time, length of stay, success rate, and post-operative hydronephrosis grading. Each approach has its particular learning curve which is significant steeper for the laparoscopic approach. Robotic assisted surgery for UPJO has been shown to be 2.7 times costlier when compared to other surgical approaches. Operating room costs were by far the greatest contributor to costs, with robotic supplies being the largest contributor to the rising cost. High volumes of RALS may be required for institutions to profit from the procedures. Conclusion: Both LAP and RAP are safe and effective procedures that can properly manage UPJO. Issues regarding finances dictates the procedure performed in our population. Pediatric urologists should be comfortable offering either of these approaches as they demonstrate high success rates in our pediatric population. Minimally invasive therapies will continue to gain popularity with future advances in laparoscopic and robotic technology.